Jalirupa dalam Lanskap Platform Seni Digital: Sebuah Purwarupa yang Menjembatani Pameran Daring dan Keterhubungan Perupa-Audiens - Ratna Cahaya Wirawan; Ester Anggun; Rani Aryani (Jurnal Sosioteknologi, 2026)
Physical exhibitions struggle to sustain networks after events conclude. While online platforms expand accessibility, they often lack immersive depth and lasting engagement. This study introduces Jalirupa, an innovative conceptual prototype. Through systematic comparative platform analysis of DeviantArt, Saatchi Art, and GAC, the study identifies a structural gap: the absence of integrated curation, long-term interaction, and emerging-artist support. Using Actor-Network Theory (Latour) and symbolic capital (Bourdieu), the research analyzes Jalirupa’s socio-technical features, such as AIassisted Q&A and aesthetic taste mapping. Findings show Jalirupa enables sustained post-event engagement, strengthens artistic brands, and offers inclusive connectivity for audiences, enriching the contemporary art ecosystem.